Hellenistic mimetic poetry - Schade, Gerson (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2016)
Since Callimachus’ mimetic hymns, super-realistic sceneries are common in Alexandrian poetry. This type of ‘realism’, however, only accompanies textual interplay. It may even be subordinated to it, as a new reading of Theocritus’ Adoniazusae (Idyll 15) suggests.